2018
DOI: 10.3390/s18124156
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Diffuse Ultrasound to Evaluation of the Water Permeability and Chloride Ion Penetrability of Cracked Concrete

Abstract: This study aims to explore the applicability of diffuse ultrasound to the evaluation of water permeability and chloride ion penetrability of cracked concrete. Lab-scale experiments were conducted on disk-shaped concrete specimens, each having a different width of a penetrating crack that was generated by splitting tension along the centerline. The average crack width of each specimen was determined using an image binarization technique. The diffuse ultrasound test employed signals in the frequency range of 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In [32], Won presented the measurement of the artificial cracks varying depth in the concrete specimens with diffuse ultrasound. Eunjong et al [33] examined the water permeability and chloride ion penetrability of cracked concrete sample using diffuse ultrasonic signal and shown that the relations between crack width, water flow, and diffuse ultrasound parameters. Considering this, the diagnosis of propagation of microcracks in reinforcement concrete remains a significant challenge for NDT techniques, despite the special interest in making such degradation since these cracks may lead to undesirable premature failure.…”
Section: Introductionmentioning
confidence: 99%
“…In [32], Won presented the measurement of the artificial cracks varying depth in the concrete specimens with diffuse ultrasound. Eunjong et al [33] examined the water permeability and chloride ion penetrability of cracked concrete sample using diffuse ultrasonic signal and shown that the relations between crack width, water flow, and diffuse ultrasound parameters. Considering this, the diagnosis of propagation of microcracks in reinforcement concrete remains a significant challenge for NDT techniques, despite the special interest in making such degradation since these cracks may lead to undesirable premature failure.…”
Section: Introductionmentioning
confidence: 99%